Structural plasticity of KIR2DL2 and KIR2DL3 enables altered docking geometries atop HLA-C - Shoeib Moradi (Nature Portfolio, 2021)
KIR2DL2 and KIR2DL3 are two inhibitory members of the killer-cell immunoglobulin-like receptors (KIR) family that share a common HLA-I preference in binding HLA from the C1 group. However, it is still unclear to what extent binding and function is equivalent between KIR2DL2 and 2DL3. Here, the authors present the crystal structures of KIR2DL2 and 2DL3 in complex with HLA-C*07:02 and observe differences in HLA-C recognition between KIR2DL2 and 2DL3, which correlates with differences in HLA-C binding preference as they show with mutagenesis and binding studies.